Improvements in exercise capacity following cardiac transplantation in a patient born with double inlet left ventricle. (5th February 2018) - Selig, Steve; Foulkes, Steve; Haykowsky, Mark
Abstract : A 32-year-old man born with double inlet left ventricle (DILV) and other significant cardiac abnormalities underwent surgical palliation at 1 day, 2 years and 20 years, before receiving a donor heart at 29 years. To our knowledge, there are no case reports or cohort studies of the effect of exercise training on exercise capacity and peak oxygen uptake (VO2 peak) following heart transplantation (HTx) for individuals born with DILV. The patient accessed our clinical exercise physiology service for assessment, advice and support for exercise training over a 7-year period spanning pre-HTx and post-HTx. An individualised exercise plan, together with careful assessment and monitoring, and the patient's own motivation have contributed to him achieving an outstanding post-HTx doubling of VO2 peak and exercise capacity.